A GMCSF and IL7 fusion cytokine leads to functional thymic‐dependent T‐cell regeneration in age‐associated immune deficiency. Issue 5 (8th May 2015) - Hsieh, Jeremy; Ng, Spencer; Bosinger, Steve; Wu, Jian Hui; Tharp, Gregory K; Garcia, Anapatricia; Hossain, Mohammad S; Yuan, Shala; Waller, Edmund K; Galipeau, Jacques
Abstract : The competence of cellular immunity depends on a diverse T‐cell receptor (TCR) repertoire arising from thymic output. Normal thymopoiesis arises from marrow‐derived CD3 − CD4 − CD8 − triple‐negative T‐cell progenitors (TN), which develop into mature single‐positive (SP) CD4 or CD8 T cells after expressing both CD4 and CD8 (double‐positive, DP) transiently, leading to de novo T‐cell production. Interleukin‐7 (IL7) is a singularly important common γ‐chain IL involved in normal thymic development. Our previous work has demonstrated that γc cytokines fused with granulocyte‐macrophage colony stimulating factor (GMCSF) at the N‐terminus acquire unheralded biological properties. Therefore, to enhance thymopoiesis, we developed a novel biopharmaceutical based on the fusion of GMCSF and IL7, hereafter GIFT7. Systemic administration of GIFT7 leads to cortical thymic hyperplasia including the specific expansion of CD44 int CD25 − double‐negative 1 (DN1) thymic progenitors. During murine cytomegalovirus (mCMV) infection of aged animals, GIFT7‐mediated neo‐thymopoiesis led to increased absolute numbers of viral‐specific CD8 + T cell. Our work demonstrated that thymic precursors can be therapeutically repopulated and its reconstitution leads to meaningful central and peripheral T‐cell neogenesis, correcting immune dysfunction arising from age‐associated thymic atrophy. Aging: A reinvigorating boost for the thymus: A fusion of two signaling proteins temporarily reverses declining function in the ageing immune system. Early in life, an organ called the thymus plays a critical role in producing diverse T cell populations that can respond to a wide variety of threats. Thymus function decreases rapidly with age, but researchers led by Jacques Galipeau of Emory University in the USA may have uncovered a strategy for jump‐starting the thymus later in life. They constructed a protein, 'GIFT7', which combines two immune‐stimulating proteins, and discovered that it stimulated both thymus cell division and T cell production. GIFT7 treatment helped elderly mice mount a robust response against viral infection, with immune activity equivalent to much younger animals. Although the rejuvenation is not permanent, even transient stimulation might protect elderly patients undergoing bone marrow transplantation against infection.